Comparisons between Classical Test Theory and Item Response Theory in Automated Assembly of Parallel Test Forms - Lin, Chuan-Ju (The Journal of Technology, Learning and Assessment, 2008)
The automated assembly of alternate test forms for online delivery provides an alternative to computer-administered, fixed test forms, or computerized-adaptive tests when a testing program migrates from paper/pencil testing to computer-based testing. The weighted deviations model (WDM) heuristic particularly promising for automated test assembly (ATA) because it is computationally straightforward and produces tests with desired properties under realistic testing conditions. Unfortunately, research into the WDM heuristic has focused exclusively on the Item Response Theory (IRT) methods even though there are situations under which Classical Test Theory (CTT) item statistics are the only data available to test developers. The purpose of this study was to investigate the degree of parallelism of test forms assembled with the WDM heuristic using both CTT and IRT methods. Alternate forms of a 60-item test were assembled from a pool of 600 items. One CTT and two IRT approaches were used to generate content and psychometric constraints. The three methods were compared in terms of conformity to the test-assembly constraints, average test overlap rate, content parallelism, and statistical parallelism. The results led to a primary conclusion that the CTT approach performed at least as well as the IRT approaches. The possible reasons for the results of the comparability of the three test-assembly approaches were discussed and the suggestions for the future ATA applications were provided in this paper.